Cold-induced elevation of homocysteine and lipid peroxidation can be alleviated by dietary folic acid supplementation - Şahin, Kazım; Onderci, M; Şahin, Nurhan; Gursu, MF; Aydin, S (Pergamon-Elsevier Science Ltd, 2003)
This study was conducted to determine the effects of folic acid supplementation at various levels on performance, carcass characteristics and serum concentrations of homocysteine. malondialdehyde (MIDA), an indicator of lipid peroxidation. folic acid. vitamin B-12. and adrenocorticotropic hormone (ACTH) in broiler Japanese quails (Coturnix coturnix japanica) reared under a low ambient temperature (6degreesC). One hundred twenty Japanese quails (10-d-old) were divided into four groups, 30 birds per group: 3 replicates of 10 birds each. The quails were fed either a basal diet or the basal diet supplemented with either 0.5, 1 or 2 mg of folic acid/kg of diet. Increased supplemental folic acid resulted in an increase in body weight (P = 0.04, linear), carcass characteristics (P = 0.01, linear), and also improved feed efficiency (P = 0.01, linear). Serum folate (P 0.02) and vitamin B-12 concentrations linearly increased (P = 0.01), whereas homocysteine (P 0.01. linear), malondialdehyde (MDA) (P = 0.01. linear) and ACTH concentrations linearly decreased (P = 0.05) as dietary folic acid supplementation increased. Results of the present study suggest that the detrimental effects of low ambient temperature on performance and serum concentrations of homocysteine and lipid peroxidation can be alleviated by dietary supple mentation with folic acid. and that the best results were obtained when 2 mg folic acid/kg,, of diet was included and folic acid supplementation at such a level can be considered as a protective management practice in a quail diet for alleviating negative effects of cold stress. (C) 2003 Elsevier Science Inc, All rights reserved.
Keywords: stress; folic acid; performance; homocysteine; MDA; vitamin B12; quail